Information and Communication Technology in Primary School Students within the Framework of Inclusive Education at a Special Basic Education Center - Vértiz-Osores, Ricardo Iván (2019)
This research aims to know the impact of information and communication technologies (ICT), as an innovative mechanism applied in curricular teaching experiences, for the development of cognitive and socio-emotional skills of students aged between 08 to 13 years from primary school who had disabilities to speak or move within the context of a Special Basic Education Center (CEBE). It was a qualitative, substantive research. The Plaphoons (free software created for special education needs) technological tool was used. The analysis of the contents of the intentions, perceptions, observation, and data registration was carried out through the triangulation of data and categorization of contents for issuing results. It was concluded that the use of this ICT enhanced the abilities of these students, confirming cognitive improvements for learning the topics of mathematical logic, communication and social sciences. It was also found that this tool allows a better and greater development of their social skills.